Bone Repair: Osteotropic Therapy via Targeted Layer‐by‐Layer Nanoparticles (Adv. Healthcare Mater. 6/2014). Issue 6 (June 2014) - Morton, Stephen W.; Shah, Nisarg J.; Quadir, Mohiuddin A.; Deng, Zhou J.; Poon, Zhiyong; Hammond, Paula T.
<x xml:space="preserve">Abstract</x> Nanomedicine that can target bone tissue for disease treatment is designed by P. Hammond and team on page 867 by modifying the surface of therapeutic‐containing particles with nanolayers of a polymer decorated with moieties that specifically bind boney regions. In this way, drug therapies can be directed to diseased bone tissue for improved treatment outcomes. LbL on nanoparticles is a versatile platform for tuning tissue specificity and therapeutic efficacy, in a controlled manner, one layer at a time. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>